2017
DOI: 10.1128/genomea.01398-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Lactobacillus plantarum 10CH, a Potential Probiotic Lactic Acid Bacterium with Potent Antimicrobial Activity

Abstract: Lactobacillus plantarum 10CH is a bacteriocin-producing potential probiotic lactic acid bacterium (LAB) strain isolated from cheese. Its complete nucleotide sequence shows a single circular chromosome of 3.3 Mb, with a G+C content of 44.51%, a 25-gene plantaricin bacteriocin gene cluster, and the absence of recognized virulence factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Many L. plantarum have been studied extensively and shown to possess broad-spectrum antimicrobial properties in different hosts ( Guerra-Ordaz et al, 2014 ; El Halfawy et al, 2017 ). However, the mechanisms underlying pathogen inhibition and interaction with the host are still not thoroughly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Many L. plantarum have been studied extensively and shown to possess broad-spectrum antimicrobial properties in different hosts ( Guerra-Ordaz et al, 2014 ; El Halfawy et al, 2017 ). However, the mechanisms underlying pathogen inhibition and interaction with the host are still not thoroughly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic bacterial growth inhibition is one of striking property of probiotics. Many studies of LAB have been shown their broad spectrum of antimicrobial activities [47,48]. The present study indicated that these Lactobacilli have ability to inhibit growth of selected common pathogens based on co-culture assays and oxford cup method.…”
Section: Discussionmentioning
confidence: 54%
“…A 180 min incubation with lysozyme is considered a severe treatment during probiotics lysozyme resistance assays [28]. The survival rate of Lactobacilli in the presence of lysozyme has also been reported by many other studies [20,28,29]. To reach the end of the GIT, stomach acid is one of the major issues for microorganisms.…”
Section: Discussionmentioning
confidence: 89%
“…A method described by Zago et al (2011) [20] was used to assess the lysozyme resistance characteristics of tested strains. Briefly, overnight culture of each strain (AR1, AR2, AR3) was centrifuged and inoculated in 9 mL of sterile electrolyte solutions (2.2 g/L KCl, 0.22 g/L CaCl 2 , 1.2 g/L NaHCO 3 , 6.2 g/L NaCl, 0.1 g/L lysozyme) to simulate in vivo dilution by saliva.…”
Section: Lysozyme Resistance Assaymentioning
confidence: 99%